(untitled) (EAAE Annual Conference Proceedings, 2023)
The high ambitions for renewable carbon technologies, increasing electricity demand and technological developments are opening more opportunities in small-scale generation. This may push zero-carbon electricity production closer to the final users/prosumers, of which the majority lives in cities and urbanised areas.